A Longitudinal Perspective on Bereaved Parent's Changes in Life Experience after the 2014 Sewol Ferry Sinking. (August 2022) - Kim, Yewon; Lee, Dong Hun; Jeon, Hong Jin
This study compared reports of parental life experiences from bereaved parents at two and five years after the death of their adolescent children due to the sinking of the Sewol Ferry in South Korea. Twelve bereaved parents (eight mothers and four fathers from eight families) were interviewed regarding the changes and stabilities they experienced over time at two time points of data collection. Twenty-eight in-depth interviews were transcribed verbatim and analyzed using qualitative content analysis. Outcomes of parental bereavement and changes in life over time may be classified into four main categories: (a) personal changes, (b) changes in perspectives, (c) changes in family relationship, and (d) changes in social relationship and work attitude. This study includes a detailed examination of the phenomenon among the bereaved parents. Discussions and implications are provided based on the results.